Cosmetic Purchasing Decisions with Brand Image as An Intervening Variable - Salsabilla Siagian; Fauzi Arif Lubis; Reni Ria Armayani Hasibuan (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2024)
Cosmetic advertisements on social media easily influence many college students, so they buy cosmetics without paying attention to the product's safety. This study aims to analyze the influence of beauty influencer variables, product quality and halal labelling on cosmetic purchasing decisions that are intervened through brand image variables. The type of research used is quantitative research with a causality research design. The population in this study is 310 respondents. Using the random sampling technique, 76 people were sampled. The data analysis technique used is path analysis. The results showed that the beauty influencer variables and halal labelling partially did not affect cosmetic purchasing decisions. However, product quality and brand image significantly affected cosmetic purchasing decisions. The variables of beauty influencers and product quality affect the brand image of cosmetics, while halal labelling does not affect the brand image of cosmetics. When intervened with the brand image variable, the two variables, beauty influencers and product quality, affect cosmetic purchasing decisions. Meanwhile, halal labelling does not affect cosmetic purchasing decisions. The implications of these results are crucial for marketers and brand managers in the cosmetic industry. Emphasizing product quality and cultivating a strong brand image can enhance purchasing decisions among consumers, particularly in a market influenced by social media. Additionally, while beauty influencers may not directly drive purchases, their impact on brand image cannot be overlooked. Companies should focus on forging relationships with reputable influencers who can authentically enhance brand perception. Future research could also explore the potential long-term effects of these variables on consumer behavior and preferences in the ever-evolving landscape of cosmetic marketing.